On the reinforcing nature of crime and punishment: An exploration of inmates' self-reported likelihood of reoffending. Issue 3 (2nd April 2016) - Schaefer, Lacey
ABSTRACT: Countering deterrence theory, recent scholarship suggests that incarceration may be criminogenic. This study theorizes that two processes influence recidivism expectations: If offending alleviates status frustration, or if criminal justice sanctions normalize deviance and instigate an identity transformation supportive of procrime values, then inmates will be more likely to report an increased likelihood of reoffending upon release. Based on self-report data from a sample of prison inmates, results indicate that a lack of life achievements and greater exposure to criminal justice sanctions discourages a commitment to desistance. Further, the psychosocial reinforcements provided by offending are positively associated with self-reported recidivism estimates.